Biodiesel synthesis using a novel monolithic catalyst with magnetic properties (K2CO3/γ-Al2O3/Sepiolite/γ-Fe2O3) by ethanolic route. (1st July 2020) - Junior, Euripedes Garcia Silveira; Justo, Oselys Rodriguez; Perez, Victor Haber; da Silva Melo, Fabiana; Reyero, Inés; Serrano-Lotina, Ana; Mompean, Federico J.
Graphical abstract: Highlights: K2 CO3 /γ-Al2 O3 /Sepiolite/γ-Fe2 O3 was prepared in monolith shape for biodiesel production. The transesterification reactions were carried out in a reactor assisted by electromagnetic field. Using this magnetic monolithic catalyst was obtained 100% biodiesel yield. Abstract: A novel magnetic monolithic catalyst based on K2 CO3 /γ-Al2 O3 /Sepiolite/γ-Fe2 O3 was developed seeking to convert efficiently soybean oil and bioethanol to ethanolic biodiesel and glycerol. The magnetic monolithic was attained by extrusion method and characterized by EPR, VSM, SEM, Dynamometry, XRD, BET, and CO2 -TPD, showing satisfactory magnetic, morphological, mechanical, structural and textural properties. The catalytic performance of this monolithic catalyst was also evaluated in a reactor assisted by magnetic field. The reactor was operated in a closed loop, recycling the reaction mixture. High oil conversion to biodiesel was obtained using 5 wt% of catalyst with 1:12 oil/ethanol molar ratio at 70 °C after 1.5 h. The magnetic properties of this monolithic catalyst allowed the bed stabilization under magnetic field and the catalysts separation, enabling its reuse by four reaction cycles.